Determinan Produktivitas Tenaga Kerja Provinsi Jawa Timur - Devita Andriani; Riko Setya Wijaya (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Labor productivity describes the total output produced by labor in a certain period of time. Based on the measurement of the level of labor productivity in regencies/cities in East Java, it is known that there are inequalities between regions. In addition, the provincial productivity level fluctuated during 2017-2021. This study aims to determine the factors that affect labor productivity with the variables studied are Dependency Ratio, Education, and Minimum Wage in 38 districts / cities in East Java Province in the period of 2017 - 2021. This study used panel data analysis which is fixed effect model is the best model. The results show that the dependency ratio variable has no effect on labour productivity. The education variable has a significant negative effect on labour productivity while the district/city minimum wage variable has a significant positive effect on labour productivity in 38 districts/cities in East Java.